La participación de la Organizaciones No Gubernamentales de desarrollo (ONGD) en las acciones sociales del Estado Municipal - Cano Quintero, María Constanza (Universidad Santiago de Cali, 2020)
The main objective is to determine the type of participation that the Non-governmental Development Organizations had when contracting with the municipality of Santiago de Cali, within the framework of developing part of their social policy. The methodology combined quantitative and qualitative information gathering techniques such as surveys and interviews. Through the investigation it was possible to verify that the participation of these organizations was between substantive and instrumental.